2020
DOI: 10.1007/s00415-020-09824-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic changes associated with frontotemporal lobar degeneration syndromes

Abstract: Objective Widespread metabolic changes are seen in neurodegenerative disease and could be used as biomarkers for diagnosis and disease monitoring. They may also reveal disease mechanisms that could be a target for therapy. In this study we looked for blood-based biomarkers in syndromes associated with frontotemporal lobar degeneration. Methods Plasma metabolomic profiles were measured from 134 patients with a syndrome associated with frontotemporal lobar degeneration (behavioural variant frontotemporal dementi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…This substance, in turn, provides apoptotic cell engulfment by macrophages 59 . Thus, increasing of LysoPS (22:6) concentration in exposed to lead group may serve as a marker of intensification of the apoptotic processes -this fact is also confirmed by the results of previous metabolomic investigations [60][61][62] .…”
Section: Metabolomic Studysupporting
confidence: 76%
“…This substance, in turn, provides apoptotic cell engulfment by macrophages 59 . Thus, increasing of LysoPS (22:6) concentration in exposed to lead group may serve as a marker of intensification of the apoptotic processes -this fact is also confirmed by the results of previous metabolomic investigations [60][61][62] .…”
Section: Metabolomic Studysupporting
confidence: 76%
“…Studies looking at the metabolic profile of FTD patients revealed dysregulation of glucose metabolism pathways on a more global scale ( Ahmed et al, 2014 ; Murley et al, 2020 ). When looking at sv-FTD and bhv-FTD patients’, the latter had lower high-density lipoprotein levels as well as increased total cholesterol levels compared to controls and both had increased triglyceride levels ( Ahmed et al, 2014 ).…”
Section: Impaired Glucose Metabolism In Frontotemporal Dementia Patientsmentioning
confidence: 99%
“…Moreover, A study involving 134 FTD patients analyzed 842 plasma metabolites and identified 49 differently altered metabolites compared to controls among FTD patients, seven were involved in energy production or carbohydrate pathways ( Murley et al, 2020 ). Observations included reduced levels of the glycolysis end product pyruvate, the TCAC intermediate succinate, glycerol-3-phosphate (a molecule pertinent to NADH re-oxidation) and glucogenic amino acids ( Murley et al, 2020 ). Whilst the first three results indicate reduced glucose metabolism activity, the last finding may point to a compensatory mechanism resulting from reduced glucose intake by cells ( Wilkins and Trushina, 2018 ; Murley et al, 2020 ).…”
Section: Impaired Glucose Metabolism In Frontotemporal Dementia Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that such studies will take place within the context of large cohort studies [see Box 6] avoiding the problems of small sample sizes that are inherent to so many of the published papers so far. Such studies will also pave the way for larger -omics studies which have so far been relatively small and focused on proteomics despite initial evidence for abnormalities in metabolomics [134][135][136] and lipidomics [137][138][139] in FTD as well.…”
Section: The Future -Clinical Trials and Treatment Responsementioning
confidence: 99%